Comparison of Descriptive English Compositions of Visually Impaired and Sighted Students in Kenyan Secondary Schools - Ombati, Jane M.; Mwangi, Phyllis W. (Machakos University, 2018)
Language is common to visually impaired and sighted students because they both use language to communicate ideas, feelings, and emotions and above all to describe their worlds. Descriptive writing brings alive the object of description, be it real or imagined. To do this effectively, it heavily exploits sensory details, sight being key among them. Descriptive essay writing is one of the topics tested in the Kenya Certificate of Secondary Examination (henceforth KCSE) that is sat by both categories of students. However, there have been few attempts to comparatively study the descriptive characteristics of English compositions of visually impaired and those of sighted students. The information is crucial in determining whether the visually impaired learners are disadvantaged in any way. This is where this paper comes in. Purposive sampling was used to select Salvation Army (S.A) Thika High School for the Visually Challenged Persons and Broadway High School, both found within Thika Municipality in Thika District, Kiambu County in Kenya. The population of the study comprised the following categories of Form Three students; the totally visually impaired, the partially sighted from S.A Thika and sighted from Broadway. Form Three and Form Four teachers of English were also part of the sample. Data was collected from descriptive compositions written by the students and from questionnaires and interview schedules administered to the sampled teachers. Compositions written by visually impaired students were debrailled. Words and phrases were then extracted from the compositions according to the various senses. They were analysed in order to determine whether they were used in equal measure by both sighted and visually impaired students. Lexical density was then calculated, data presented in tables and results discussed. The findings in this paper revealed that visually impaired students used fewer descriptive terms in total and in all the senses than their sighted counterparts. The sighted students predominately exploited the sense of sight in their description while the visually impaired students mainly used the sense of hearing. The paper further established that even if all the sensory details used by the visually impaired students were combined, they would not match with the ones obtained from the sense of sight among the sighted students. The paper therefore concluded that there is a true correlation between sightedness and descriptive writing. The following recommendations were made: that the teachers deliberately present as many first-hand descriptive concepts in class as possible to the visually impaired students; schools for the visually impaired consider admitting sighted students to learn together with the visually impaired for more linguistic input; KNEC consider adapting descriptive composition topics to avoid disadvantaging the visually impaired students.
Keywords: Descriptive writing; Visually impaired students